2003
DOI: 10.1109/tmag.2003.815440
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic printing technique for perpendicular thin-film media with coercivity of up to 10 000 Oe

Abstract: A magnetic printing technique designed for perpendicular thin-film media using a lithographically formed master disk has been presented. It is shown that magnetic printing using perpendicular hard-disk media with high coercivities of up to 10 000 Oe is satisfactorily carried out and practical printing conditions for perpendicular recording media are discussed by analyzing differences in the magnetization processes during printing processes designed for perpendicular and longitudinal media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Ishida et al demodulated the signals from a head flying across the grooves and found the position error in a prototype drive was 30% of the track pitch, or 0.41 µm [191]. The printing technique has also been extended to perpendicular recording media having H c as high as 10 kOe using a soft Co film magnetic mask [192]. Experiments on double layer slave disks have also been reported, where one layer has high coercivity and contains the printed information and the second, softer, layer acts as the recordable medium [193].…”
Section: Patterned Servomentioning
confidence: 99%
“…Ishida et al demodulated the signals from a head flying across the grooves and found the position error in a prototype drive was 30% of the track pitch, or 0.41 µm [191]. The printing technique has also been extended to perpendicular recording media having H c as high as 10 kOe using a soft Co film magnetic mask [192]. Experiments on double layer slave disks have also been reported, where one layer has high coercivity and contains the printed information and the second, softer, layer acts as the recordable medium [193].…”
Section: Patterned Servomentioning
confidence: 99%
“…The other is the method that uses the horizontal magnetic field. The horizontal magnetic field induces the vertical components at the down track edges of master pattern and prints the servo pattern on a PMR media [1]. We call the former method as "bit printing (BP)," and the latter as "edge printing (EP).…”
Section: Bit Printingmentioning
confidence: 99%
“…Also, a perpendicular magnetic printing [1]- [4], which can write servo signals with high speed, high accuracy, and low cost, has been studied.…”
Section: Introductionmentioning
confidence: 99%